El humor polaco en la realidad española: los juegos de palabras en ,, Ostatnie życzenie " de Andrzej Sapkowski y su traducción por José María Faraldo - Koszarska, Maja (Wydawnictwo Naukowe UAM, 2007)
The translation of humour is a challenge. It requires the accurate decoding of a humorous speech in its original context, the transfer of that speech in a different linguistic and cultural environment and its reformulation in a new expression, which recaptures the intention of the original message. The actual work attempts to present the nature of puns, which constitute one of the manifestations of humour in the literature, in its linguistic and cultural dimension. The study is based on a comparative analysis of examples of puns from Ostatnie życzenie of Andrzej Sapkowski and its Spanish translation. The results are compared in terms of equivalence in linguistic, stylistic and cultural properties to show a risk of loss of the transtextual and transcultural elements and the way of recompensing these elements by substitution, amplification and other rhetorical techniques.
Polish (sense of) humour in Spanish reality: play on words (puns) in Andrzej Sapkowski's "Last wish" as translated by José María Faraldo
Keywords: Humour in the literature; Ostatnie życzenie; Sapkowski Andrzej; Spanish translation; Translation